Interest rates and asset prices - Turvey, Ralph (New York : Macmillan, 1961)
This book presents a statement of the theory of asset price formation, aimed at setting out a theory which meets three requirements in relation to ordinary economic theory.
sju 23/01/2019
Loans
Keywords: Prices; Interest